A novel multi-omics approach for identifying key genes in intervertebral disc degeneration - Xuan Zhao; Qijun Wang; Shuaikang Wang; Wei Wang; Xiaolong Chen; Shibao Lu (SLAS Technology)
Many different cell types and complex molecular pathways are involved in intervertebral disc degeneration (IDD). We used a multi-omics approach combining single-cell RNA sequencing (scRNA-seq), differential gene expression analysis, and Mendelian randomization (MR) to clarify the underlying genetic architecture of IDD. We identified 1,164 differentially expressed genes (DEGs) across four important cell types associated with IDD using publicly available single-cell datasets. A thorough gene network analysis identified 122 genes that may be connected to programmed cell death (PCD), a crucial route in the etiology of IDD. SLC40A1, PTGS2, and GABARAPL1 have been identified as noteworthy regulatory genes that may impede the advancement of IDD. Furthermore, distinct cellular subpopulations and dynamic gene expression patterns were revealed by functional enrichment analysis and pseudo-temporal ordering of chondrocytes. Our results highlight the therapeutic potential of GABARAPL1, PTGS2, and SLC40A1 targeting in the treatment of IDD.